Syntheses, structures and properties of a series of photochromic hybrids based on Keggin tungstophosphates - Zhang, Li-Zhi (2012)
Three inorganic–organic hybrids based on Keggin tungstophosphates and lanthanides, [Pr(NMP)6(PW12O40)]n (1), [Eu(NMP)6(PW12O40)]n (2), and [Er2(NMP)12(PW12O40)][PW12O40] (3) (NMP=N-methyl-2-pyrrolidone), have been synthesized and characterized by elemental analysis, IR, UV–vis, and single-crystal X-ray diffraction. Compounds 1 and 2 exhibit 1D infinite zigzag chain structures, while compound 3 exhibits an ionic asymmetric structure due to lanthanide contraction. The three compounds are all photochromic. The magnetic susceptibility for 1 measured over the range 2–300 K shows that there is the dominant antiferromagnetic interaction in the compound. The results of luminescent properties show that compound 2 displays an interesting selectivity for Zn2+ ions.